The Relationship Between Maternal Knowledge, Exclusive Breastfeeding History, and Infectious Diseases with the Incidence of Underweight in Telukjambe Village - Devina, Adinda Rahma; Elvandari, Millyantri; Sefrina, Linda Riski (PROMOTOR, 2025)
Based on SSGI 2022 data, the prevalence of underweight children in Indonesia has increased from the previous year, which amounted to 17.1%. Underweight is a condition where body weight (BB/U) is not in accordance with age. This study aims to analyze the relationship between maternal knowledge, exclusive breastfeeding history, and infectious diseases on the incidence of underweight toddlers in Telukjambe village. The type of research used is quantitative research with descriptive methods of cross sectional design. The results of bivariate analysis obtained a p-value> 0.05, which can be interpreted that there is no relationship between maternal knowledge, exclusive breastfeeding history, and infectious diseases with the incidence of malnutrition in Telukjambe village.